2021
DOI: 10.1097/tp.0000000000003962
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Convalescent Plasma to Treat Mild to Moderate COVID-19 in Kidney Transplant Patients: A Propensity Score Matching Analysis

Abstract: Supplemental Digital Content is available in the text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 5 publications
1
20
0
Order By: Relevance
“…Because no benefit in disease progression or death was observed among the first 58 treated patients, compared with a propensity-scored matched control group, the study was prematurely terminated. 7 Similar findings were observed in an international multicenter trial in nontransplanted patients, which was also terminated because of the lack of efficacy. 8 We had no access to other agents providing passive immune protection, such as the monoclonal antibodies directed against SARS-CoV-2, although to date, there are no data regarding the efficacy of these agents in transplanted patients.…”
supporting
confidence: 70%
“…Because no benefit in disease progression or death was observed among the first 58 treated patients, compared with a propensity-scored matched control group, the study was prematurely terminated. 7 Similar findings were observed in an international multicenter trial in nontransplanted patients, which was also terminated because of the lack of efficacy. 8 We had no access to other agents providing passive immune protection, such as the monoclonal antibodies directed against SARS-CoV-2, although to date, there are no data regarding the efficacy of these agents in transplanted patients.…”
supporting
confidence: 70%
“…Green text indicates trials which met the primary endpoint with statistical significance; orange text indicates trials which failed to meet the primary endpoint but showed statistically nonsignificant trends in favor of CCP; red text indicates trials which failed to show and benefit from CCP in the primary endpoint. Sources cited in the figure are references 9 12 , 26 30 , 34 36 , 41 , 46 , 48 , 50 , 52 , 57 , 73 , 76 , 77 , 113 , 144 , and 145 . Numbers in parentheses represent the number of recruited patients.…”
Section: The Indicationmentioning
confidence: 99%
“…Although this low mortality was likely multifactorial, one feature of this cohort was that 44 of 77 (57%) received convalescent plasma. 47 To overcome the limitations of case series, Cristelli et al 64 performed a propensity-matched cohort study in kidney transplant recipients with COVID-19, in which 58 of 456 (13%) of patients received a single unit of convalescent plasma at a median of 6 d from symptom onset, and 116 others were selected as controls. The authors found no differences in survival, oxygen requirement, or mechanical ventilation; however, the convalescent plasma used was not uniformly high-titer, and there was a trend toward a higher proportion of survivors receiving hightiter plasma.…”
Section: Convalescent Plasmamentioning
confidence: 99%
“…The authors found no differences in survival, oxygen requirement, or mechanical ventilation; however, the convalescent plasma used was not uniformly high-titer, and there was a trend toward a higher proportion of survivors receiving high-titer plasma. 64 Senefeld et al 65 pooled data from 75 published studies reporting on immunocompromised patients who had received convalescent plasma through April 2021, and reported that overall, this provided evidence for mortality benefit and rapid clinical improvement. The pooled data included 66 SOT recipients, of whom 14% died and 68% had rapid improvement in supplemental oxygen requirements.…”
Section: Convalescent Plasmamentioning
confidence: 99%